2013
DOI: 10.1371/journal.pone.0080737
|View full text |Cite
|
Sign up to set email alerts
|

PRICKLE1 Interaction with SYNAPSIN I Reveals a Role in Autism Spectrum Disorders

Abstract: The frequent comorbidity of Autism Spectrum Disorders (ASDs) with epilepsy suggests a shared underlying genetic susceptibility; several genes, when mutated, can contribute to both disorders. Recently, PRICKLE1 missense mutations were found to segregate with ASD. However, the mechanism by which mutations in this gene might contribute to ASD is unknown. To elucidate the role of PRICKLE1 in ASDs, we carried out studies in Prickle1+/− mice and Drosophila, yeast, and neuronal cell lines. We show that mice with Pric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 58 publications
2
55
0
Order By: Relevance
“…Vangl2 and Prickle2 also bind and promote postsynaptic clustering of PSD95, critical for maintenance of synaptic integrity [199,227,228]. Prickle1 was found to regulate synaptogenesis and synaptic vesicle trafficking through a direct interaction with synapsin1 (Syn1) [229]; the synapsin protein family have important roles in synapse formation and neurotransmitter release and have previously been implicated in the pathogenesis of psychiatric disorders [230,231,232,233,234,235,236]. Indeed, Prickle1 +/- mice exhibit ASD-like behaviors, and expression of a mutant form of Prickle in cultured cells phenocopies the vesicle trafficking defect observed with aberrant Syn1 function [229].…”
Section: Synapse Formation and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vangl2 and Prickle2 also bind and promote postsynaptic clustering of PSD95, critical for maintenance of synaptic integrity [199,227,228]. Prickle1 was found to regulate synaptogenesis and synaptic vesicle trafficking through a direct interaction with synapsin1 (Syn1) [229]; the synapsin protein family have important roles in synapse formation and neurotransmitter release and have previously been implicated in the pathogenesis of psychiatric disorders [230,231,232,233,234,235,236]. Indeed, Prickle1 +/- mice exhibit ASD-like behaviors, and expression of a mutant form of Prickle in cultured cells phenocopies the vesicle trafficking defect observed with aberrant Syn1 function [229].…”
Section: Synapse Formation and Functionmentioning
confidence: 99%
“…Prickle1 was found to regulate synaptogenesis and synaptic vesicle trafficking through a direct interaction with synapsin1 (Syn1) [229]; the synapsin protein family have important roles in synapse formation and neurotransmitter release and have previously been implicated in the pathogenesis of psychiatric disorders [230,231,232,233,234,235,236]. Indeed, Prickle1 +/- mice exhibit ASD-like behaviors, and expression of a mutant form of Prickle in cultured cells phenocopies the vesicle trafficking defect observed with aberrant Syn1 function [229]. While upstream Wnt ligands involved in these events remain to be identified, these studies provide additional evidence that components of the Wnt/PCP pathway are critical contributors to synapse formation and function.…”
Section: Synapse Formation and Functionmentioning
confidence: 99%
“…Mutations in PRICKLE1 disrupt its ability to increase the size of synaptic vesicles. Studies suggest that PRICKLE1 mutations contribute to ALB and seizures by disrupting the interaction with synapsin 1 and the regulation of synaptic vesicles, thus leading to abnormalities in the E/I ratio (Paemka et al 2013(Paemka et al , 2015.…”
Section: Genetics Of Epilepsy and Autismmentioning
confidence: 99%
“…Indeed, we found that the postnatal deletion of Vangl2 initiated at P7 resulted in an increase in glutamatergic synapses, measured at P14. Because mutations of some PCP components, such as Prickle1 and Prickle2, have been implicated in autism and epilepsy, precisely pinpointing the function of PCP signaling components will lead to better understanding of the synaptopathy underlying many neurological and neuropsychiatric disorders (21)(22)(23)(24).…”
mentioning
confidence: 99%